The Role of Inflation and The Performance of Rural Banks on Indonesia’s Economic Growth - Saat, Tito Arfandi; Harahap, Erni Febrina (Gorontalo Development Review, 2024)
The purpose of this study is to evaluate the impact of inflation and Rural Banks' (BPR) performance—that is, their assets, credit, and third-party funding—on Indonesia's economy. For the years 2014–2020, panel data regression using a fixed effect model approach is the technique employed. Secondary data from the Financial Services Authority (OJK), Central Statistics Agency (BPS), and other relevant organizations were used in this investigation. The findings indicated, in part, that the credit variable had a significant coefficient value of 0.119, the inflation variable had a significant coefficient value of -0.033, the asset variable had a significant coefficient value of -0.006, and the third party fund variable had an insignificant coefficient value of 0.064. At the same time demonstrating how the variables of assets, third-party funding credit, and inflation all influence Indonesia's economic variables at the same time. A coefficient of determination of 0.99 is attained. Then, these findings demonstrate that the variables of inflation, assets, credit, and third-party funds account for 99 percent of the variation in economic variables' growth and fall, with other factors outside the model influencing the remaining 1%.